Safety Knowledge of Welding Workers in The Manufacturing Industry - Hassim, Ahmad Munsif; Rozali, Mohd Zulfadli (Research and Innovation in Technical and Vocational Education and Training, 2022)
Safety knowledge aspect is a very important aspect to prevent accidents. This problem arises due to workers lacking knowledge of safety knowledge. The purpose of this study is to identify the safety knowledge of welding workers in the manufacturing industry in Pasir Gudang, Johor. This study has six objectives, which is to identify aspects of safety knowledge in terms of regulation, environment, responsibilities, hand tools use, machines use and the relationship between aspect of safety knowledge towards the safety practice of welding workers in the manufacturing industry. Research design for this study is quantitative survey method. A total of 70 participants were selected as samples of the study comprising welding workers in five manufacturing industries in Pasir Gudang, Johor. This finding will be analyzed using Statistical Package for Social Science version 26.0 and the data analyzed using descriptive statistical methods to find the value of the mean score and the standard deviation. Based on the analysis, the results showed that the safety knowledge of welding workers in the manufacturing industry was at a moderate level where the safety knowledge aspect in terms of regulations (M = 2.88, SP = 0.116), environment (M = 2.98, SP = 0.153), responsibility (M = 2.89, SP = 0.150), use of hand tools (M = 2.89, SP = 0.174) and machine use (M = 2.87, SP = 0.230). Meanwhile, the analysis of the relationship between aspects safety knowledge of welding workers on the practice safety of welding workers in the manufacturing industry using the inferential analysis method (Pearson-r) to find the value of correlation. Based on the analysis, the Pearson-r correlation value showed that the relationship between safety knowledge aspects of the rules was 0.566, environment was 0.898, responsibility was 0.869, hand tool use was 0.531 and machine use was 0.741. Overall, based on the findings, it can be concluded that the employee safety knowledge on the safety practice of welding workers in the manufacturing industry is at the highest level.